SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2118/84038-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Relationships between Residual Gas Saturation and Initial Gas Saturation in Heterogeneous Sandstone Reservoirs

Abstract: Residual gas saturation is considered to be a key factor in evaluating gas recovery from a lean gas reservoir invaded by water. Residual gas saturation is known to be dependent on both pore network characteristics and initial gas saturation. In this paper, sixty experimental relationships between initial gas saturation (Sgi) and residual gas saturation (Sgr) are presented for a large set of sandstone samples and checked against former empirical Sgr-Sgi laws. Previously, no more than two authors have presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…The plot indicates that within the considerable scatter of the data -caused by taking results from different rock types and fluid systems -there is an increase in trapping capacity with initial saturation. The solid lines are fits to experiments on sandpacks that suggest an approximately linear relationship between trapping capacity with initial saturation, followed by a constant value, as also found by Suzanne et al (2003).…”
Section: Experiments Of Capillary Trappingsupporting
confidence: 62%
See 1 more Smart Citation
“…The plot indicates that within the considerable scatter of the data -caused by taking results from different rock types and fluid systems -there is an increase in trapping capacity with initial saturation. The solid lines are fits to experiments on sandpacks that suggest an approximately linear relationship between trapping capacity with initial saturation, followed by a constant value, as also found by Suzanne et al (2003).…”
Section: Experiments Of Capillary Trappingsupporting
confidence: 62%
“…This could be caused by natural groundwater flow, buoyancy-driven upwards migration of the CO 2 plume or deliberate injection of brine (chase brine) to trap the Co 2 . The residual saturation increases with initial saturation while it usually decreases with increasing rock porosity (Jerauld, 1997;Suzanne et al, 2003). in this discussion we will focus on experiments that have studied water-wet systems, where the trapped oil (or gas, or Co 2 ) is the non-wetting phase.…”
Section: Experiments Of Capillary Trappingmentioning
confidence: 99%
“…Such air is referred to as 228 "entrapped air" (Faybishenko, 1995). Suzanne et al (2003) measured the amount of 229 entrapped air using Fontainebleau sandstone having a porosity of 8.5% and reported that 230 air was trapped in 69% and 38% of the pore space for init S = 6% and 50%, respectively. 231…”
mentioning
confidence: 99%
“…Capillary trapping has been measured in oil/water, gas/water, and three-phase gas/water/oil systems; Figs. 1 and 2 show a compilation of two-phase data in the literature (Geffen et al 1952;Crowell et al 1966;Pickell et al 1966;Land 1968Land , 1971McKay 1974;Ma and Youngren 1994;Jerauld 1997;Kleppe et al 1997;Kralik et al 2000;Suzanne et al 2003;Al Mansoori et al 2009a), while Table 1 gives a summary of the associated parameters for each study.…”
Section: Introductionmentioning
confidence: 99%
“…Ma and Youngren observed that, at higher initial gas saturations, there was a sharp leveling off of the trapped-gas saturation. This led to the introduction of two empirically derived curve-fitting constants, a and b, where b = 1 and a = C in Land's original correlation: Other studies (Kleppe et al 1997;Suzanne et al 2003) have questioned the validity of applying Land's trapping relationship to rock/fluid systems other than those analyzed by Land-consolidated rock with a strongly water-wet gas/liquid system where the initial saturation was established by evaporation rather than by displacement. A shortcoming of the Land equation (Eq.…”
Section: Introductionmentioning
confidence: 99%